Die Nederduitsch Hervormde Kerk van Afrika as volkskerk: Oorsig en herbesinning - Dreyer, W.A. (HTS teologiese studies, 2006)
The Nederduitsch Hervormde Kerk van Afrika as “volkskerk”: Overview and evaluationThe Church Order of the Nederduitsch Hervormde Kerk van Afrika (NHKA) states in Ordinance 4 that the NHKA is a “volkskerk”, meaning a Church that is ethnically based and focused on the ministry to Afrikaans speaking people. This article examines the history of the relationship between NHKA and Afrikaners that prevailed since the early 19th century. It argues that the establishment of separate and ethnically based churches in South Africa was, initially, the result of a specific understanding of Afrikaner nationalism and liberty. Only after the Second World War, due to criticism levelled at separate development and separate churches by the ecumenical movement, it was based on theological reflection. This article concludes that the term “volkskerk” has become theologically obsolete as well as practically unusable.